Burn-up Analysis of TRIGA MARK II Research Reactor Fuel Elements Using OpenMC Program - Prasetya, Fajri (Indonesian Journal of Physics, 2024)
The TRIGA 2000 Bandung research reactor, a TRIGA MARK II type that has been operating critically since 1946, has experienced a significant decrease in criticality. This prompted researchers to implement a reshuffling scheme of 111 fuel elements to optimize burn-up throughout the reactor core area. Burn-up analysis of the TRIGA 2000 Bandung fuel elements has been carried out. This analysis aims to determine the burn-up capability and isotope production of each individual fuel element. The calculation uses the Monte Carlo-based OpenMC code that has gone through the verification and validation (V&V) stage based on the results of the MCNP simulation at 60% control rod withdrawal. Furthermore, the reactor power is varied by 100kW-500kW to see the reactor's ability to maintain criticality (k-eff) and obtain very small excess reactivity (ρ). The calculation of k-eff and ρ for 1 year (12 months) is applied in 2 ways, namely 5 hours per week and real-time. The results of real-time operations can optimize burn-up to near the critical point. The greater the power, the greater the number of neutrons for fission, thus accelerating the consumption of fissile material. The power of 200 kW was chosen for further analysis because at the end of the burn-up, the k-eff and ρ values ​​approached the critical point. The results of the percentage of U-235 and U-238 burn-up to be greater in the middle area of ​​the reactor core (ring B) and consistently decreased towards the edge of the reactor core (ring G). As a result, the mass production of Pu-239 was also very high in the ring B area. This also happened to toxic isotopes such as Sm-149, Xe-133, Xe-135 which tended to be high in that area. The high burn-up rate and isotope production became a reference for future research to apply the reshuffling concept to the TRIGA 2000 Bandung reactor core